2005
DOI: 10.1080/09540120412331336652
|View full text |Cite
|
Sign up to set email alerts
|

Patients referred to an urban HIV clinic frequently fail to establish care: factors predicting failure

Abstract: To measure the success with which patients newly entering outpatient care establish regular care, and assess whether race/ethnicity was a predictive factor, we conducted a medical record review of new patients seen 20 April 1998 to 31 December 1998 at The Thomas Street Clinic, a county clinic for uninsured persons. Patients were considered 'not established' if they never saw a physician in the 6 months after intake (the 'initial period'), 'poorly established' if seen but a > 6-month gap in care began in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
124
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 20 publications
8
124
3
1
Order By: Relevance
“…35,39,40 Other studies indicate that adolescents and young adults are less likely to link and remain in care than older adults. [40][41][42] Some studies using different age ranges for analysis found no difference in linkage in younger adults. 35,[43][44][45] However, combining published data from these studies (Table 1), we estimate that 62% of newly diagnosed HIV-infected adolescents and young adults in the United States link to care within the first 6-12 months.…”
Section: Linkage To Carementioning
confidence: 99%
“…35,39,40 Other studies indicate that adolescents and young adults are less likely to link and remain in care than older adults. [40][41][42] Some studies using different age ranges for analysis found no difference in linkage in younger adults. 35,[43][44][45] However, combining published data from these studies (Table 1), we estimate that 62% of newly diagnosed HIV-infected adolescents and young adults in the United States link to care within the first 6-12 months.…”
Section: Linkage To Carementioning
confidence: 99%
“…YLHIV are more likely to disengage from care, delay initiation of antiretroviral therapy (ART), and have lower rates of virologic suppression on ART. [3][4][5][6][7][8][9] YLHIV face barriers to care that are unique to the developmental period of adolescence and young adulthood. 10,11 Like many youth with chronic illness, YLHIV must learn to cope with a chronic medical condition at a time when most peers are healthy.…”
mentioning
confidence: 99%
“…To date, with two exceptions, 33,37 studies of barriers to HIV care entry have been retrospective. [38][39][40][41][42][43][44] Never in Care Pilot interviews with people who had not yet entered care at the time of the interview show that barriers to care are multidimensional, and indicate that poverty and mental health problems may be contributing factors, underscoring the importance of supportive services to help with starting and staying in care.…”
Section: Discussionmentioning
confidence: 99%